2020
DOI: 10.1097/icb.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Improvement of Syphilis Chorioretinitis: Case Report and Review of the Literature

Abstract: Spontaneous improvement of syphilis chorioretinitis is possible. Clinicians should keep a high index of suspicion and consider syphilis chorioretinitis in diseases that affect the outer retina even with spontaneous improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The first successful DMEK surgery was performed more than a decade ago,7 and while the number of DMEK procedures being performed rose every year between 2012 and 2016, as per data provided by the Eye Bank Association of America, widespread adoption of the technique by corneal surgeons has been slow, because of the perceived difficulty of the procedure 1,8. In our study, we found steps related to graft preparation, graft insertion, and unfolding as being the most difficult to learn by corneal surgeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first successful DMEK surgery was performed more than a decade ago,7 and while the number of DMEK procedures being performed rose every year between 2012 and 2016, as per data provided by the Eye Bank Association of America, widespread adoption of the technique by corneal surgeons has been slow, because of the perceived difficulty of the procedure 1,8. In our study, we found steps related to graft preparation, graft insertion, and unfolding as being the most difficult to learn by corneal surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found greater cell loss in the S-stamp area in preloaded DMEK grafts, often with complete loss of all cells in the stamped area 14. DMEK presents a steep learning curve and surgical skills that are entirely different from DSEK 8. Experienced DSEK surgeons may not be as compelled to learn DMEK, especially when they might be achieving satisfactory results with their current technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spontaneous resolution of SOR has also been described. 5 ASPPC has been more commonly reported than SOR as a posterior segment manifestation of ocular syphilis, and the effect of oral steroids on ASPPC is also controversial. Ormaechea et al 7 described a case of ASPPC in which oral steroids resulted in the resolution of the placoid retinal lesions when an initial diagnosis of autoimmune disease was incorrectly made; however, vitritis and exudative retinal detachment worsened and penicillin was eventually required for the complete resolution of ocular findings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Indeed, in four of the seven cases published to date, SOR was initially diagnosed as acute zonal occult outer retinopathy and two of these cases presented with normal fundus examination. [2][3][4][5] Syphilitic outer retinitis can present with minimal funduscopic changes; however, outer retinal abnormalities can be identified on fundus autofluorescence imaging and OCT. [2][3][4] Hyperreflective nodularity of the RPE is a feature of both ASPPC and SOR that may help raise suspicion for syphilis and distinguish SOR from acute zonal occult outer retinopathy, as might the presence of vitreous cell. 4,6 Additional potential distinguishing features of acute zonal occult outer retinopathy include a demarcation line most apparent on fundus autofluorescence and a trizonal pattern on multimodal imaging.…”
Section: Discussionmentioning
confidence: 99%